2009
DOI: 10.35172/rvz.2009.v16.388
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de sensibilidade de bactérias isoladas de animais domésticos na região de botucatu frente ao cloranfenicol e florfenicol

Abstract: O advento dos antimicrobianos permitiu o controle e cura das doenças infecciosas, mudando aevolução natural das mesmas de forma marcante. Os resultados de programas locais de vigilância deresistência a antimicrobianos são de extrema importância, pois auxiliam a escolha da terapêuticaempírica, especialmente em infecções no qual o diagnóstico etiológico é difícil. No caso específico daterapêutica antimicrobiana em animais de companhia, sabe-se da importância do cloranfenicol, peloseu amplo espectro de ação e pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The results found that all tested isolates were sensitive to chloramphenicol with the formation of a 37 mm inhibition halo. These findings have proved to be common, since different studies have already demonstrated the sensitivity of different groups to chloramphenicol (Paes et al, 2023;Cruz et al, 2021). The CP2 strain was also sensitive to tetracycline with the formation of a 27 mm zone of inhibition and the isolate CP2.1 was sensitive to the antibiotic erythromycin with a 31 mm zone.…”
Section: Resultsmentioning
confidence: 90%
“…The results found that all tested isolates were sensitive to chloramphenicol with the formation of a 37 mm inhibition halo. These findings have proved to be common, since different studies have already demonstrated the sensitivity of different groups to chloramphenicol (Paes et al, 2023;Cruz et al, 2021). The CP2 strain was also sensitive to tetracycline with the formation of a 27 mm zone of inhibition and the isolate CP2.1 was sensitive to the antibiotic erythromycin with a 31 mm zone.…”
Section: Resultsmentioning
confidence: 90%